THE REASONS FOR FEASIBILITY OF USING A SUBLIMATION DRYING PROCESS OF RAW MATERIALS IN THE MANUFACTURE OF CULINARY PRODUCTS OF HIGH NUTRITIONAL VALUE - Sofia Vyacheslavovna Gusarova; Milana Olegovna Vasilyeva; Anastasia Mikhaelovna Timofeeva (Современная наука и инновации, 2022)
One of the best technology of food preservation is sublimation drying, which is a physical process of transition of a substance from solid to gas, bypassing the liquid phase. The authors demonstrated the feasibility of using a sublimation drying process of raw materials in the manufacture of culinary products of high nutritional value.